1968
DOI: 10.1111/j.1432-1033.1968.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Phytoquinones. Stereospecific Biosynthesis of the Polyprenyl Side Chains of Terpenoid Quinones and Chromanols in Maize Shoots

Abstract: The incorporation of (3RS)‐[2‐14C,(4R)‐4‐3H1]mevalonic acid and (3RS)‐[214‐C,(4S)‐4‐3H1]‐mevalonic acid into plastoquinone, ubiquinone, γ‐tocopherol, α‐tocopherol, α‐tocopherol quinone, β‐carotene, squalene and 3β‐hydroxysterols by maize shoots has been studied. In agreement with the findings of workers using other tissues the atomic 14C/3H ratios for β‐carotene, squalene and 3β‐hydroxysterols labelled from [2‐14C,4R‐3H1]mevalonic acid are found to be 8:6, 6:6 and 5:3. When [2‐14C,4S‐3H1]mevalonic acid is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1968
1968
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Although the biochemical pathway for the synthesis of tocopherols has been proposed for some time, the inherent difficulties of working with such membrane‐bound enzymes have prevented a good understanding of the biochemical regulation of this pathway from being achieved. The traditional approach of using isolated chloroplasts and labelled compounds to study tocopherol synthesis was highly effective in deciphering the general biosynthetic pathway,58–61 but these studies have provided little insight into the regulation of tocopherol composition or carbon flux through the pathway. For example, virtually nothing is known about the enzymes controlling the availability/production of major pathway precursors (HGA, phytyl‐PP, GGPP, solanyl‐PP), the branch point enzyme in the pathway common to tocopherol/plastoquinone synthesis (the Arabidopsis Pds2 gene product), or the methylase enzymes involved in determining tocopherol composition.…”
Section: Biosynthesismentioning
confidence: 99%
“…Although the biochemical pathway for the synthesis of tocopherols has been proposed for some time, the inherent difficulties of working with such membrane‐bound enzymes have prevented a good understanding of the biochemical regulation of this pathway from being achieved. The traditional approach of using isolated chloroplasts and labelled compounds to study tocopherol synthesis was highly effective in deciphering the general biosynthetic pathway,58–61 but these studies have provided little insight into the regulation of tocopherol composition or carbon flux through the pathway. For example, virtually nothing is known about the enzymes controlling the availability/production of major pathway precursors (HGA, phytyl‐PP, GGPP, solanyl‐PP), the branch point enzyme in the pathway common to tocopherol/plastoquinone synthesis (the Arabidopsis Pds2 gene product), or the methylase enzymes involved in determining tocopherol composition.…”
Section: Biosynthesismentioning
confidence: 99%
“…Threlfall, Griffiths & Goodwin (1967b) and Dada, Threlfall & Whistance (1968) showed that the polyprenyl portions of these compounds are formed from mevalonic acid, and Threlfall, Whistance & Goodwin (1967a) demonstrated that the methyl group of methionine is transferred intact to give the nuclear methyl group of phylloquinone, the nuclear methyl group and two methoxyl groups of ubiquinone and one or more nuclear methyl groups of plastoquinone, y-tocopherol, a-tocopherol and atocopherolquinone. The results for the incorporation of radioactivity from L-[Me-14C,3H]methionine into plastoquinone, tocopherols and tocopherolquinones also led to the conclusion that one nuclear methyl group in each of these compounds is not derived from methionine (see the Results section).…”
mentioning
confidence: 99%
“…(1966Whistance ct al. ( , 1967 and Whistance and Threlfall (1968) found that radioactivity from shikimic acid-'''C labelled either generally or in the positions 1 and 2 was incorporated into the naphthoquinone nucleus of phylloquinone in maize shoots {Zea mays L.).…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear methyl group of phylloquinone has been shown to arise from the S-methyl group of methionine in maize shoots and in leaves of Hedera helix L. (Threlfall et al 1968, Whistance and. In maize shoots this methylation involves the transfer of an intact methyl group from methionine, and the reaction appears to take place in the chloroplast ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation